Organisasi Massa Islam Awal Abad 20; Telaah Terhadap Perjalanan Gerakan Sarekat Islam - Abdullah Khusairi (IAIN Padangsidimpuan, 2019)
This article reveals the journey of an Islamic mass organization in the early 20th Century, Serikat Dagang Islam (SDI), which later became Serikat Dagang (SI). This organization was present as a form of awareness to unite in the movement to deal with the economic pressures of the Dutch East Indies government. In the early days of its presence it was not intended to be a political tool of power but SI activists eventually became figures respected by the Dutch East Indies government at that time. The momentum of the rise of thought and the independence movement of the Negara Kesatuan Republik Indonesia (NKRI) actually started from SI activists who spread in various developing regions. They are active in writing thoughts in the print media that are being loved by Muslim cum activists. These activists networked with each other in producing discourse in written form and owning their respective media. This article would like to offer that every movement through the organization as a vehicle for Da'wah Islamiyah must prepare activists who are capable, brave, and strong in fighting. More than that, it is able to design and implement the latest Da'wah Islamic strategy in the midst of the political currents that are in power so as not to lose and sink in the midst of the times that keep changing so fast.